DIFFERENCES IN MANIFESTATION OF EXPLOSIVE POWER OF LEGS REGARDING TO LONGITUDINAL FOOT ARCH IN YOUNG ATHLETES - Ilona Mihajlović; Miloš Petrović; Milan Šolaja (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
It is known that various postural deformities affect the eficiency of motor abilities, especilly if the status of longitudinal foot arch, which indirectly affects the whole locomotive system. Previous studies have different approaches and conclusions regarding this issue. Our research was conducted on sample of 75 boys, aged 11-12, participants of athletic school in Novi Sad. Variables'sample consisted of two motor tests: standing long jump and running at 20 meters from high start. The foot status of participants was determinated, in terms of the existence of possible longitudal arch deformities. Based on these variables the total participants' sample is devided in two sub-samples (group 1 & group 2). Measurement of motor abilities was performed by standard protocol with the written consent of parents. The foot status was determined by using computerised digitalised podography. By using MANOVA, ANOVA and discriminant analysis we came to the results that there are no statistically significant differences in the manifestation of motor abilities which are responsibile for explosive strength and speed between boys with and without deformities.